Wind and rainfall erosion energy in large sediment generating and coarse sediment class areas of the middle Yellow river - Tao Yang; Jianzhi Niu; Dengxing Fan; Di Wang; Yubo Miao; Miao Wang; Chunguang Zhao; Linus Zhang; Xiongwen Chen; Ronny Berndtsson (International Soil and Water Conservation Research, 2025)
Joint action by strong winds and high-intensive rainfall leads to serious soil erosion problems in large sediment generating and coarse sediment class areas of the middle Yellow River. Investigating the variation of trend and alternating wind and rainfall energy is an important prerequisite for controlling regional sediment transport problems. We calculated the wind and rainfall erosion energies by using the aerodynamic energy and rainfall kinetic energy formulas. The Mann-Kendall (MK) trend test and Theil-Sen approach were used to analyze the spatial-temporal variation and alternation of joint erosion energy during the last 40 years (1979–2018). The results show the following. 1) Wind erosion energy increased and rainfall erosion energy decreased. However, the former is larger than the latter. 2) The dominant erosive energy varies for different seasons. Wind erosive energy dominates in spring, and rainfall erosive energy dominates in summer. 3) There is a regular wind-rainfall-wind alternation of erosive energy. The wind-rainfall energies were alternately distributed in May–July and the rainfall-wind energies were alternately distributed in September–December. Furthermore, the dominant time of rainfall erosive energy decreased when wind erosive energy increased. The results can help decision makers to develop soil erosion control strategies to reduce soil erosion when it occurs in wind and water staggered areas.